2020
DOI: 10.1200/jco.19.02446
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes and Retreatment Among Patients With Previously Treated, Programmed Death-Ligand 1‒Positive, Advanced Non‒Small-Cell Lung Cancer in the KEYNOTE-010 Study

Abstract: PURPOSE In the KEYNOTE-010 study, pembrolizumab improved overall survival (OS) versus docetaxel in previously treated, programmed death-ligand 1 (PD-L1)‒expressing advanced non‒small-cell lung cancer (NSCLC) in patients with a tumor proportion score (TPS) ≥ 50% and ≥ 1%. We report KEYNOTE-010 long-term outcomes, including after 35 cycles/2 years or second-course pembrolizumab. METHODS Of 1,033 patients randomly assigned (intention to treat), 690 received up to 35 cycles/2 years of pembrolizumab 2 mg/kg (n = 34… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
187
1
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(196 citation statements)
references
References 15 publications
3
187
1
5
Order By: Relevance
“…Anti-PD(L)1 immune checkpoint inhibitors (ICI) singly or in combination with anti-CTLA-4 or other agents are approved across multiple indications in sixteen separate diseases including a histology-agnostic indication in patients with microsatellite instability-high (MSI-H) or mismatch repair deficient (dMMR) solid tumors. 1,2 The hallmark of ICI therapy is the durability of responses in a subset of patients as evidenced by progression-free survival (PFS) rates of 21-29% in melanoma and 22% in non-small cell lung cancer (NSCLC) with anti-PD(L)1 singly; [3][4][5][6][7] and up to 36% with anti-PD-1/anti-CTLA-4 dual ICI in melanoma. 8 However, the majority of patients do relapse and the question of how to improve outcomes in these patients remains a vexing problem for the field.…”
Section: Introductionmentioning
confidence: 99%
“…Anti-PD(L)1 immune checkpoint inhibitors (ICI) singly or in combination with anti-CTLA-4 or other agents are approved across multiple indications in sixteen separate diseases including a histology-agnostic indication in patients with microsatellite instability-high (MSI-H) or mismatch repair deficient (dMMR) solid tumors. 1,2 The hallmark of ICI therapy is the durability of responses in a subset of patients as evidenced by progression-free survival (PFS) rates of 21-29% in melanoma and 22% in non-small cell lung cancer (NSCLC) with anti-PD(L)1 singly; [3][4][5][6][7] and up to 36% with anti-PD-1/anti-CTLA-4 dual ICI in melanoma. 8 However, the majority of patients do relapse and the question of how to improve outcomes in these patients remains a vexing problem for the field.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with these results, previous studies have shown that the biological processes of the immune system are critical to the formation of a complicated LUAD tumor microenvironment 10,30,[37][38][39] . In the past few years, the understanding of the immunological characteristics of LUAD has increased, and the development of effective LUAD immunotherapy strategies has drawn wide attention [40][41][42][43][44] .…”
Section: Discussionmentioning
confidence: 99%
“…Despite the imperfection of PD-L1 TPS due to heterogeneity, it has proven to be an independent predictive biomarker of response to immune-checkpoint inhibitors in guidance of first and second line treatment in advanced NSCLC [2][3][4][27][28][29][30][31]. Improvement in median PFS from 6.0 months (95% CI, 4.2− 6.2) with chemotherapy to 10.3 months (95% CI, 6.7-NR) with pembrolizumab has changed first line treatment algorithm in advanced NSCLC patients with PD-L1 TPS ≥50% [27,28].…”
Section: Progression Free Survivalmentioning
confidence: 99%
“…Second line treatment of advanced NSCLC is largely independent of PD-L1 TPS, according to European Society of Medical Oncology (ESMO) Clinical Practice Living Guidelines of Metastatic Non-Small-Cell Lung [32], although the type of immune-checkpoint inhibitor therapy can be affected. Hence, second line pembrolizumab is only recommended if PD-L1 TPS is ≥1% according to results of the KEYNOTE-010 study [29,30], and atezolizumab/nivolumab can be administered regardless of PD-L1 TPS according to results of the CHECKMATE 017/057 [2,3] and OAK trials [4,31]. These guidelines are primarily based on studies with no mandatory new biopsy for PD-L1 TPS analyses, although in KEYNOTE-010 (including patients with PD-L1 TPS ≥ 1%), a protocol amendment required a new biopsy for PD-L1 TPS, except when it risked patient safety.…”
Section: Pd-l1 Tpsin Second Line Treatment Guidancementioning
confidence: 99%